Managing the laboratory animal facility - Silverman, Jerald (CRC Press, 2002)
Most people in research are elevated into managerial positions because of their skills as scientists and their political acumen, not necessarily because of managerial training or experience. This book helps managers in training and those who are looking for help in applying basic concepts of managing a laboratory animal facility.